Pengeluaran Pemerintah Untuk Pertumbuhan Ekonomi Indonesia - Hana, Wiara; Prasetyanto, Panji Kusuma (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2021)
This study aims to determine the effect of central government spending, debt interest payments, and subsidies on economic growth in Indonesia. This study also uses annual data for 1990-2019 obtained from the Ministry of Finance of the Republic of Indonesia (Kemenkue RI), BPS, and Financial Notes. The model used in this study is the Error Correction Model (ECM). Based on the results of the study, it can be concluded that simultaneously central government spending, debt interest payments and subsidies have a significant and significant effect on GDP (Gross Domestic Product) in Indonesia both in the long and short term and the variables of central government spending and subsidies have a significant effect on economic growth in Indonesia. in the short and long term, while the variable interest payments on debt has no significant effect on economic growth in Indonesia in the short and long term.